The altruism equation : seven scientists search for the origins of goodness - Dugatkin, Lee Alan, 1962- (Princeton University Press, 2006)
In a world supposedly governed by ruthless survival of the fittest, why do we see acts of goodness in both animals and humans? This problem plagued Charles Darwin in the 1850s as he developed his theory of evolution through natural selection. Indeed, Darwin worried that the goodness he observed in nature could be the Achilles heel of his theory. Ever since then, scientists and other thinkers have engaged in a fierce debate that has dragged politics, philosophy, and religion into what remains a major question for evolutionary biology." From the bookjacket.